2017
DOI: 10.1159/000478023
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Electrophysiologic Subthalamic Nucleus Length as a Predictor of Outcomes in Deep Brain Stimulation for Parkinson Disease

Abstract: Background: Intraoperative measurement of subthalamic nucleus (STN) width through microelectrode recording (MER) is a common proxy for optimal electrode location during deep brain stimulation (DBS) surgery for Parkinson disease. We assessed whether the MER-determined STN width is a predictor of postoperative Unified Parkinson Disease Rating Scale (UPDRS) improvement. Methods: Records were reviewed for patients who underwent single-sided STN DBS placement for Parkinson disease between 2005 and 2010 at the UAB M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Some centers use one MER and adding more if needed, the single sequential approach, usually using the length of STN signals as a criterion. However, there is no certain significant relationship between STN length and UPDRS improvement . Also, with this approach, it may be difficult to recognize too medially placed electrodes .…”
Section: Introductionmentioning
confidence: 99%
“…Some centers use one MER and adding more if needed, the single sequential approach, usually using the length of STN signals as a criterion. However, there is no certain significant relationship between STN length and UPDRS improvement . Also, with this approach, it may be difficult to recognize too medially placed electrodes .…”
Section: Introductionmentioning
confidence: 99%
“…At present, intraoperative measurement of subthalamic nucleus width via microelectrode recording is a common proxy for optimal electrode location during deep brain stimulation (DBS) surgery for patients with Parkinson's disease (12). However, to the best of our knowledge, the role of PAI-1 in evaluating the therapeutic effects of DBS has not been investigated in patients with Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported an average error of 2.2 mm in the X-coordinate and of 2.0 mm in the Y-coordinate that would have corresponded to misplaced DBS electrode placement in ~20% of all DBS implants, had MER not been performed [51], but this study was poorly controlled. Although Shenai et al [52] found a 58% improvement in post-op UPDRS scores with MER mapping, no statistical difference was found for STN spans of <4.8 mm as compared to >5.6 mm. However, in all 73 cases, MER did confirm that the target was within the dorsolateral STN.…”
Section: Subcortical Mapping Using Microelectrode Recording For Dbs Placementmentioning
confidence: 88%